Revisiting the Concept of Development, Disaster and Safety Management: The Quranic Perspective - Badhrulhisham, Abdul Aziz; Azizan, Ramli; Mazlin, Mokhtar (Elsevier, 2014)
Economic development is accompanied by the use of an increasingly complex technology, especially in the process of industrialization. The technological threats will cause an unpredictable event such as industrial accident or even the worst scenario, industrial disaster. Thus, the purpose of this paper is to provide an overview linking the literature on how Islam views the objective of development as well as the industrial disaster and safety management system. To our knowledge, most of the studies with regard to disaster and safety management are technical and administrative oriented. The angle of spirituality and religiosity is always being disassociated, especially with what commonly is regarded as worldly affairs. In this paper we tried to discuss what Islam says about industrial disaster and safety of industrial activities and how it relates to Allah׳s commandment. We also highlighted the story about disasters from the Quran in brief and drawn the lessons learned. The risk assessment process relating to safety matter was also discussed alongside the priority (-awlawiyyat) and comparison (-muqaranah) approach. The sources of information are academic articles and books, religion texts, and internet websites. To this end, in order to incorporate the spiritual approach into the industrial disaster and safety management system, the tripartite concepts of vicegerency (-al-istikhlaf), cooperation for righteousness (-al-ta’awun) and consultation (-shura) are introduced.